Determinants of loan repayment among agricultural microcredit finance group members in Delta state, Nigeria - Solomon Enimu; Emmanuel O. Eyo; Eucharia A. Ajah (Financial Innovation, 2017)
Background: This study examined the determinants of loan repayment among microcredit finance group members in Delta State, Nigeria. Methods: To capture the determinants of loan repayment in the study area, a total of 48 microcredit groups and 300 microcredit group members were randomly selected through a multi-stage random sampling technique. The study data was collected by questionnaire. Statistical tools such as simple descriptive statistics (table, frequency, percentage and mean) and a multiple regression analysis were used to examine the data. Results: The results indicate that females form a greater proportion of the study area microcredit group members at 70%, moreover 73% of the respondents have a household size of between 6 to 10 persons. These findings revealed that the groups had a mean 8 years of existence with a mean membership size of 13 persons. Further, an average interest rate of 40 percent per annum was charged on loans, with mean loan duration of 6 months. The regression's result demonstrated that the determinants of the group member's loan repayment included the group member's age, household size, house income, and educational level, the amount of credit received, length of stay in their locality, distance to the credit source, supervision and disbursement lag. Conclusion: Therefore it was suggested that the various agricultural microcredit finance groups should carefully examine the significant determinants of loan repayment for the approach's viability and sustainability and for optimum repayment performance.
Keywords: 650; Determinants; Loan repayment; Microcredit; Groups; Members; Delta state